Manajemen Proyek Pengembangan Sistem Informasi Penjualan Buku Berbasis Web untuk Meningkatkan Efisiensi Operasional - Nursa’adah; Yahfizham (Journal Of Informatics And Busisnes, 2024)
Modern technology has developed rapidly and can produce extraordinary benefits in various fields, including the advancement of information. Accurate, relevant, and reasonable information is highly valued in the workplace. By reducing errors and maximizing data administration, data frameworks. Advancing operational adequacy by combining innovation and human activity to support operations and administration. Books continue to be popular, especially among young people who enjoy reading heartfelt stories. High demand and low purchasing costs encourage companies to improve information management. However, many bookstores still use manual recording, which is inefficient and prone to errors. A computerized inventory system is essential for effective data management. Manual book sales management is time-consuming and prone to errors. In this study, the author uses the waterfall method for developing the system and for the data collection method using interview, observation, and heritage study methods. The purpose of this study is the need for an online book transaction data structure to reduce information loss, prevent exchange errors, and provide information in real-time. It is expected that the use of this framework will significantly increase productivity in preparing information and ensuring accurate and secure exchange.